Β-Pyridylenolate zinc catalysts for the ring-opening homo- and copolymerization of ε-caprolactone and lactides. Issue 30 (7th July 2017) - Bai, Jianliang; Xiao, Xia; Zhang, Yue; Chao, Jianbin; Chen, Xia
Abstract : Eleven zinc β-quinolylenolates with varying substituents have been synthesized, and some of these complexes are excellent catalysts for the ring-opening homo- and copolymerization of ε-CL and LAs. Abstract : A family of zinc β-pyridylenolates with varying α, β-substituents has been synthesized. A direct reaction of β-pyridyl ketone ligands with ZnEt2 in toluene afforded dimeric [LZnEt]2 (L = (2-C5 H4 N)–C(R 1 )C(R 2 )–O–). X-ray structural data revealed that all the [LZnEt]2 complexes exist as μ-O-bridged dimers in the solid state, although they adopt a different geometry. Each of the [LZnEt]2 complexes is a highly active catalyst for the ring-opening polymerization (ROP) of ε-caprolactone (ε-CL) and racemic lactide ( rac -LA), respectively. The donating group on the enolate ligand can accelerate the ROP reaction and control the polymerization process well. All complexes also showed different abilities in the block and random copolymerization of ε-CL andl -LA. Diblock PCL- b -PLLA and PLLA- b -PCL copolymers were easily prepared via sequential addition of ε-CL andl -LA by using complex10, respectively. Random copolymers of PCL- ran -PLLA were also synthesized from complex10 . The copolymers of PCL- ran -PLLA were shown to possess monomer contents which matched well with their composition in the monomer feed. NMR and DSC characterization confirmed a highly random structure of these copolymers, resulting in closely average lengths of the caproyl and lactidyl sequences ( L CL = 2.1; L LA = 1.9). All zinc complexes as efficient single-component initiators in both homo- and copolymerizations showed that polymers were probably susceptible to chain transfer and transesterification due to the close Zn⋯Zn proximity in the dimer. The polymers initiated by [LZnEt]2 in the absence of BnOH showed high molecular weight and narrow molecular weight distributions.